Intervenção Pedagógica para ensino de leitura, escrita e aritmética para uma criança com implante coclear - Barbosa, Regiane da Silva (Universidade Federal de São Carlos, 2015)
The cochlear implant (CI) consists of an effective technological resource in the treatment of deafness. The surgery for the CI has been performed by the time children are still one year old. Therefore, the number of deaf children with CI included in the Brazilian education has also increased. Thus, it is crucially important to know and reflect on the education of deaf children with CI included in regular school. They are subjects of special education and might have various special educational needs, which entitle them to specialized educational services. As it has been stated, the present study is based on the following guiding questions: What are the main difficulties that children with CI face in the acquisition of reading and writing? What are the main difficulties that children with CI face in arithmetic? Which activities can contribute to the acquisition of reading, writing and arithmetic by children with CI? To answer these questions the present research aims to apply and analyze pedagogical interventions for the teaching and learning of reading, writing and arithmetic of children with cochlear implants by developing specific activities which can contribute to the achievement of such aim. The development of the research took place through an exploratory, longitudinal, qualitative case study, which had as participant a seven-year-old female child with bilateral profound hearing loss who has been a CI-user since she was three years old. The child in question, in addition to facing the challenges commonly associated with deaf children with CI such as the development of oral language, the development of reading and writing skills as well as inclusion in education, has a peculiar life history: she was born overseas and came to Brazil at the age of seven, after the global economic crisis of 2009. In the Results section, the activities carried out with the child at the Special Education Laboratory of a university in a medium-sized city in the State of São Paulo are described. The activities carried out with the child, based on Gotti (1992) and Costa (1994), were prepared in accordance with her needs and difficulties by aiming at the acquisition of oral language, reading and writing skills in Portuguese and at the acquisition of arithmetic. Visual aids and dramatization resources were used in every intervention session. In the Final Considerations section, the advances and the child’s learning are described, in addition to the main difficulties encountered by her, which consisted of producing texts in Portuguese, interpreting texts and statements of arithmetic activities. Not only has the use of visual aids and drama been effective in the teaching and learning of deaf children, as it is well explored in the concerning literature, but also in the teaching and learning of deaf children with CI. The CI was instrumental in the development and learning of the participating child, because not only did it enable her to develop oral language, but also two languages, an eastern one and the Portuguese language. Furthermore, it enabled her to learn and acquire knowledge and information through such language and, therefore, establish oral communication and socialize, which resulted in her inclusion in the family, at school and in society. In addition to suggestions of work and teaching and learning activities, greater investment in research on the education of children with CI is recommended, thus contributing to national research and to the education and success of these children.
Keywords: Educação especial; Surdez; Implante coclear; Ensino - aprendizagem; Leitura e escrita; Aritmética; Special Education; Deafness; Cochlear Implant; Teaching and Learning; Reading and Writing; Arithmetic; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO